Hubungan kualitas Website UPI Central Library dengan kepuasan pengguna - Ricky Hardiyanto; Ninis Agustini Damayani; Edwin Rizal (Faculty of Communication, Padjadjaran University, 2021)
The times and the role of information technology require libraries to innovate, one of the innovations made by libraries is a website. Website quality is currently a strategic issue that is used in communication and interaction with users. This research is intended to know quality of UPI Central Library Website relation with user satisfaction, especially bachelor students of Indonesia University of Education in the main campus of Bumi Siliwangi. One method of measuring the quality of a website can be done by using WebQual. This study uses the WebQual 4.0 method as the basis for measuring the quality of the web proposed by Barnes & Vidgen which consists of of usability, information quality, and service interaction quality. Meanwhile in order to measure user satisfaction uses the theory of importance-performance analysis by Martilla and James which consist of importance and performance. The method is use is Quantitative Method with correlational treatment Pearson Product Moment which is intended to treat causality between X and Y variables. The collecting data technique used questionnaires, interviews and literature studies. Sampling was conducted by simple random sampling technique using a population of 27,172 students and respondents as many as 394 students. The results of this study indicate that the web quality of the UPI Central Library on user satisfaction has a significant relationship, which means that the higher the quality of the web, the higher the satisfaction received.